2010
DOI: 10.1074/jbc.m110.121913
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin-conjugating Enzyme UbcM2 Can Regulate the Stability and Activity of the Antioxidant Transcription Factor Nrf2

Abstract: The transcription factor nuclear factor E2-related factor 2 (Nrf2) induces the expression of antioxidant gene products that neutralize reactive oxygen species and restore redox homeostasis. Nrf2 is constitutively degraded by the ubiquitin proteolytic system in unperturbed cells, but this turnover is arrested in response to oxidative stress, thereby leading to Nrf2 accumulation. Yet, a mechanistic understanding of how Nrf2 stabilization and transcriptional activation are coupled remains to be determined. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 46 publications
3
47
0
Order By: Relevance
“…Moreover, phosphatidylinositol 3-kinase could contribute to the depolymerization and disruption of the actin cytoskeleton, concomitant dysregulation of KEAP1 and subsequent NRF2 nuclear accumulation [27]. In addition, a recent study suggested that the ubiquitin conjugating enzyme UBCM2, through its function as a redox sensor, can enhance NRF2 stability and activity during oxidative stress [28]. The nuclear import and export of KEAP1 and/or NRF2 leads to the cytoplasmic-nuclear shuttling of NRF2 [29].…”
Section: Reviewmentioning
confidence: 97%
“…Moreover, phosphatidylinositol 3-kinase could contribute to the depolymerization and disruption of the actin cytoskeleton, concomitant dysregulation of KEAP1 and subsequent NRF2 nuclear accumulation [27]. In addition, a recent study suggested that the ubiquitin conjugating enzyme UBCM2, through its function as a redox sensor, can enhance NRF2 stability and activity during oxidative stress [28]. The nuclear import and export of KEAP1 and/or NRF2 leads to the cytoplasmic-nuclear shuttling of NRF2 [29].…”
Section: Reviewmentioning
confidence: 97%
“…The Neh1 domain contains the bZIP motif, which allows Nrf2 to bind to the antioxidant response element (ARE) sequence. In addition, this domain can interact with E2 ubiquitin conjugating enzyme to regulate the Nrf2 protein stability [51]. The Neh2 domain, located in the most N-terminal region, acts as a negative regulatory domain by binding to the Nrf2 inhibitor Keap1 [45].…”
Section: The Keap1-nrf2 Pathwaymentioning
confidence: 99%
“…When a cell is exposed to oxidative stress, Nrf2 dissociates from the Keap1/Cul3 complex and translocates into the nucleus, leading to activation of ARE-mediated gene expression [188]. A recent study indicates that a specific ubiquitin conjugating enzyme, UbcM2, acts as a redox sensor and a regulator of Nrf2 activation [189]. When the function of the UPP was impaired or inhibited, Nrf2 accumulated in cells and activated the expression of many antioxidant enzymes [186, 190192].…”
Section: Interaction Between the Upp And Cellular Antioxidant Systemsmentioning
confidence: 99%